2013
DOI: 10.1111/jfbc.12057
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Structure and Bioactivity of Recombinant Fungal Immunomodulatory Protein, Ling-Zhi-8 (LZ-8) Following Exposure to Denaturing Conditions

Abstract: Ling-Zhi-8 (LZ-8), a low-molecular weight protein from Ganoderma lucidum, exerts immunomodulatory effects in vitro and in vivo. The aim of this study was to investigate the effects of exposure of LZ-8 to denaturing conditions on its ability to suppress inflammatory responses in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Ultraviolet, fluorescence and circular dichroism spectroscopy analyses showed that LZ-8 was not denatured by exposure to pH extremes, but was irreversibly denatured by temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that FIP possess broad spectrum immunomodulatory and anticancer activities, suggesting that they may be promising candidates in clinical disease therapies or for treatment as adjuvant agents 4,17 . FIP can be orally consumed and have high stability when exposed to denaturing conditions 18,19 . These characteristics make FIP a potential candidate to be used as an additive in the health food industry.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that FIP possess broad spectrum immunomodulatory and anticancer activities, suggesting that they may be promising candidates in clinical disease therapies or for treatment as adjuvant agents 4,17 . FIP can be orally consumed and have high stability when exposed to denaturing conditions 18,19 . These characteristics make FIP a potential candidate to be used as an additive in the health food industry.…”
Section: Discussionmentioning
confidence: 99%
“…That means they are rather digestion-resistant, or that some vital domain, responsible for their bioactivity, reaches the intestinal tract intact. In some articles, the thermal stability and digestion resistance of FIPs have been described ( 111 , 118 120 ). Additional research will deliver details about essential domains as well as their utilization.…”
Section: Prospectsmentioning
confidence: 99%